Drowning tides - Harper, Karen (Karen S.) (Harper, Karen (Karen S.) South Shores., 2017)
When forensic psychologist Claire Britten started working with lawyer Nick Markwood on his South Shores project, she had no idea it would endanger her life<U+2014>and the life of her daughter. But when the little girl goes missing from her South Florida home and Nick insists his longtime nemesis is to blame, Claire frantically follows the trail to the Cayman Islands, desperate to save her daughter before it's too late. Nick always knew the man who staged his father's "suicide" was out to get him, but kidnapping the child of someone he cares about is despicable. Finding the billionaire criminal is one thing<U+2014>meeting his demands in order to save Claire's daughter is quite another. What he wants threatens their professional and personal interests beyond imagination<U+2026>but what choice do they have when a child's life is on the line?